(untitled) (Orthodontic Journal of Nepal, 2022)
Introduction: Malocclusion is one of the most important oral health problems among children and young adults, leads to social stigma and psychological disorders. Early detection of orthodontic disorders is essential in motivating patients to intervene prior to long-term complications when the disorders are not recognized. The aim of this study is to determine and evaluate the knowledge and attitude of general dentists and non-orthodontic specialists towards early orthodontic treatment. Materials and Method: A total of 240 dentists and other specialists than orthodontists participated in the study. A questionnaire consisting of 3 domains having 17 items was circulated using Google forms. The responses were collected further coded and analysed to assess the knowledge and attitude scores. Data was entered in SPSS (v.21.0) and statistical analysis was performed. (p<0.05) Result: A total of 122 general dentists and 122 non-orthodontic specialists responded to the questionnaire. The results showed that the non-orthodontic specialist had a higher mean knowledge score of 7.2 as compared to general dentists (6.1). Furthermore, both the study participants had a positive strong attitude towards improving their knowledge in early orthodontic treatment. Conclusion: The study highlights the need of better education for treatment concepts in orthodontics to the general dentist and non-orthodontic specialist.